Appearance of the Optic Nerve in Glaucoma Detection - Terry Ponte, Ruty (1998)
Between December 1995 and May 1996, 725 patients were evaluated in the Ophthalmology Department of the Central Hospital of the National Police of Peru. Ophthalmological examination including determination of intraocular pressure was carried out, the evaluation of the appearance of the optic nerve and visual field. Casuistry of 1.96% of newly diagnosed glaucoma, ocular hypertension 12.27% and 6.71% of patients with disc pseudoglaucomatosa relationship was found. The search for glaucoma in eye health campaigns, QUC is based solely on high values ​​of intraocular pressure, can improve the sensitivity and specificity significativamcnte further evaluated whether the appearance of the optic nerve.